Effectiveness of Different Orthoses on Joint Moments in Patients with Early Knee Osteoarthritis： Lateral Wedge Versus Valgus Knee Bracing - 张旻 瞿珮育 冯美兰 江澜 沈晓艳 马燕红 白跃宏 (Shanghai jiao tong da xue xue bao, 2012)
The purpose of the study was to test the biomechanical differences between a lateral wedge and a valgus knee bracing on the knee joint moment during walking in patients with early stage of medial compartment knee osteoaxthritis （OA）. We conducted a crossover randomized design to compare gait parameters of 32 patients （with early stage medial compartment knee OA） in three different conditions during walking： with a custom-made lateral wedge of 5 （in standard shoes）, with a valgus knee bracing （in standard shoes）, and with control condition （in standard shoes）. Both two-orthose conditions showed decreased loading patterns （knee adduction moment and knee adduction angular impulse） on the knee joint in dynamic condition （statistic probability P ~ 0.05）. The decreased loading on OA knee in wedge condition was associated with a laterally shifted location of centre of pressure and increased ankle valgus degree and moment at the same foot （P 〈 0.05）. It was not found significant differences in loading of the knee between these two-orthose conditions. These results indicated that, under dynamic condition, patients wearing lateral wedge and valgus knee bracing showed changes of moments on knee joints. Lateral wedge was as effective as valgus knee bracing in the treatment of early stage of knee OA.